From science-fiction to realism: on Dmitry Glukhovsky’s writing - Kozak, Ewa (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2018)
The article brings an analysis of Dmitry Glukhovsky’s science-fiction writing from the perspective of realistic motifs and the writer’s striving for realism. In his novels and short stories the writer touches upon real problems of the contemporary Russian society: helplessness of an ordinary man in the face of the system, corruption, censorship, falsified election results, iniquity, impunity. Glukhovsky brings up such issues in his Tales about the Motherland and his novels Futu.re, Metro 2035, thus reaching beyond science-fiction. The same problems become the focus of his attention in his latest, realistic novel Text.